Representing Transnational Drug Trafficking: Narcos (2015) and the War on Drugs Narrative - Widiarti, Widiarti; Argenti, Gili (Journal of Integrative International Relations, 2026)
This study analyzes Netflix’s Narcos (2015-2017) as a cultural text representing transnational drug trafficking and the war on drugs narratives within International Relations frameworks. Employing qualitative interpretive analysis of selected episodes alongside International Relations and media scholarship, it reveals how the series personalizes complex structural dynamics for instance globalization-driven crime into charismatic antiheroes such as Pablo Escobar, portrays Colombian institutions as fragile and reliant on U.S. DEA (Drug Enforcement Administration) agents, and reproduces securitized war on drugs discourses without challenging root causes such as Global North demand. These representations simplify transnational threats, mythologize violence as spectacle, and reinforce Global North-South asymmetries in security imaginaries